Factors influencing government insurance scheme beneficiary acceptance of the gatekeeper policy: a cross-sectional study in Wuhan, China - Wenzhen Li; Dongming Wang; Yong Gan; Yanfeng Zhou; Yawen Chen; Jing Li; Naomiem Kkandawire; Sai Hu; Yan Qiao; Zuxun Lu (BMC, 2018)
Abstract Background Gatekeeper policy, requiring a patient to visit a primary care provider first, and the patient needs to get his or her primary care provider's referral before seeing a specialist or going to a hospital, has been implemented in China for about ten years, and it is necessary to assess the patients' acceptance of gatekeeper policy and to explore the factors influencing patients' acceptance. Methods A cross-sectional study with 1162 respondents was conducted between July and September 2015 at four community health centers (CHCs) in Wuhan, China. Face-to-face interview was used to collect information on demographics, acceptance of the gate keeper policy and satisfaction with community health services. Patients' satisfaction with community health service was evaluated using the European Patients Evaluate General/Family Practice scale and binary logistic regression model was used to examine the factors influencing patients' acceptance of community health services as gate keepers. Results A total of 512 (43.06%) patients accepted gatekeeper policy. Mandatory reimbursement provision (OR: 1.63, 95% CI: 1.23-2.15), patient satisfaction with the aspects of medical care (OR: 1.92, 95% CI: 1.12-3.29) and organization of care (OR: 1.66, 95% CI: 1.05-2.62) were associated with acceptance of gatekeeper policy, after adjusting for potential confounders. Moreover, young people (OR: 0.35, 95%CI: 0.22-0.56) seemed to be more reluctant to accept the policy, when compared with the elder. Conclusions Our study suggests that mandatory reimbursement provision greatly affects patients' acceptance of gatekeeper policy, therefore, the policy-maker should pay attention to the negative effect of its mandatory reimbursement provision on patients' acceptance of the policy. However, improving the aspects of medical care and organization of care will contribute to implementation of gatekeeper policy.